Mitigation Actions by the Marine Epas Against the Oil Spill on the Northeast Brazilian Coast - Célia Macedo do Nascimento, Regina Célia Macêdo; Sousa, Fernanda Vale de; Vicente, Caroline Pardi; Catojo, Adriana Maria Zalla (Costas, 2023)
Brazil has established Marine Conservation Units to safeguard its biodiversity and regulate the use and occupation of these regions. They are considered a coastal zone, thereby being susceptible to disasters such as the oil spill that affected the Brazilian coast in 2019. Thus, the present research aimed to verify whether the management plans of the affected Environmental Preservation Areas (EPA) included contingency measures for chemical accidents involving oil, as well as the actions taken by government environmental agencies in terms of the assistance provided. Considering the organizations/institutions involved in the beach cleaning assistance, we sought to identify whether the actions taken for beach cleaning were related to tourism. To achieve this, we conducted searches on the platforms of the Socio-Environmental Institute (ISA), Chico Mendes Institute for Biodiversity Conservation (ICM Bio), Brazilian Institute of Environment and Renewable Natural Resources - IBAMA, State Secretariats of Environment and Tourism, and the respective State Governments’ portals. As a result, thirteen EPAs were found in the states of Bahia, Pernambuco, and Rio Grande do Norte. No management plans mentioned oil spills; however, the actions carried out during the incident were punctual and effective, mitigating major impacts on biodiversity and socio-economic aspects, as the beaches are tourist attractions and sources of income for the municipalities. This factor motivated quicker actions to prevent larger impacts on the municipalities’ economy and environment. Therefore, revisions of the management plans should include provisions for such incidents, enabling decision-making to be more concise and even faster and effectively address the damages to these environments. .